2019
DOI: 10.1007/s10067-019-04859-w
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge level of rheumatoid arthritis patients about their disease in a developing country. A study in 168 Bangladeshi RA patients

Abstract: Objectives To assess disease-related knowledge of rheumatoid arthritis (RA) patients Patients and methods Consecutive RA patients were invited from the rheumatology departments of BSMM University, Dhaka, Bangladesh. The Bangla version of the Patient Knowledge Questionnaire (B-PKQ) was used. Correlations between the B-PKQ scores and clinical-demographic data were measured using Pearson's correlation coefficient. Impact of independent variables on the level of knowledge about RA was analyzed through multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Also, several authors reported the use of exercise, joint protection, and energy conservation as the least-known topics. [ 23 - 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Also, several authors reported the use of exercise, joint protection, and energy conservation as the least-known topics. [ 23 - 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, better disease control of RA may be achieved by improving patient knowledge of the disease (11). The need for information and decision-making was higher in women than in men and younger age, and greater knowledge of RA predicted a greater need for decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Several knowledge questionnaires (KQs) are available in the literature. The Patient Knowledge Questionnaire, which was developed in 1991 and validated again in 2004 [ 10 , 11 ] and the Knowledge Questionnaire, which dates from 1997 [ 12 ], have both been used in several studies [ 14 17 ]. However, they were constructed before the era of targeted disease-modifying anti-rheumatic drugs (DMARDs).…”
Section: Introductionmentioning
confidence: 99%